Evidence for an association between the aetiology of cirrhosis and pattern of hepatocellular carcinoma development. Issue 1 (1st January 2001) - Benvegnù, L; Noventa, F; Bernardinello, E; Pontisso, P; Gatta, A; Alberti, A
Abstract : BACKGROUND: Patients with liver cirrhosis are at significant risk of hepatocellular carcinoma (HCC) that may develop as well defined nodular lesions or as more aggressive infiltrating tumours. AIM: To compare prospectively risk factors associated with nodular or infiltrating HCC in cirrhotic patients. PATIENTS AND METHODS: We studied 370 patients with cirrhosis, followed prospectively by periodic ultrasound (US) of the liver, for a mean period of 74.6 (SD 32.4) months to define the incidence and patterns of HCC development. Patients who developed HCC were compared according to tumour pattern using univariate and multivariate analysis. RESULTS: Sixty one (16.5%) patients developed HCC: HCC was classified as nodular in 49 (80.3%) and infiltrating in 12 (19.7%) according to US and computerised tomography (CT) imaging. The five and 10 year cumulative probabilities were 8.1% (95% confidence interval (CI) 5.2%-11%) and 25.2% (15.0–35.4%) for nodular HCC and 2.1% (0.5–3.7%) and 6.9% (2.1–11.7%) for infiltrating HCC. Patients with infiltrating HCC were younger than those with nodular HCC (59.5 v 66.2 years, 95% CI 55.2–63.8 and 64.1–68.3 years; p=0.014). Using multivariate analysis, development of nodular HCC was associated with older age (p=0.0002; relative risk (RR) 3.1; 95% CI 1.6–5.2), longer duration (p=0.09; RR 2.6; 95% CI 1.8–3.4), and more advanced stage (p=0.002; RR 2.5; 95% CI 1.3–4.5) of cirrhosis but not with the aetiology of liver disease. In contrast, development of infiltrating HCC appeared to be unrelated to age or disease duration or stage, while it was associated with hepatitis B virus infection (p=0.07; RR 3.96; 95% CI 1.1–5.2) and with hepatitis B/hepatitis C virus coinfection (p=0.0007; RR 16.9; 95% CI 3.8–36.7). CONCLUSIONS: In liver cirrhosis, we identified two patterns of HCC developing with distinct risk factors. Nodular HCC was related to the cirrhotic process per se independent of aetiological factors and may depend on the proliferative activity within regenerative nodules, while the infiltrating form of HCC was linked to hepatitis B virus infection and may reflect more direct virus induced carcinogenesis.